The Effect of Education, Health and Per Capita Income on Poverty Rate in Maluku Province - Salong, Erni; Bugis, Muhammad; Tonny Matitaputty, Izaac; Ramly, Fahrudin (PT Mattawang Mediatama Solution, 2024)
Poverty is a common phenomenon that occurs in all countries and at all times. This study aims to determine the factors that allegedly affect poverty in Maluku Province such as the level of education, health and per capita income. Data obtained from the Central Statistics Agency in the form of data on average length of schooling (RLS), life expectancy (AHH), per capita income and poverty rate. The method used is multiple liear regression. The results showed that RLS had a significant negative effect on the poverty rate while AHH and per capita income had a negative and significant effect on reducing the poverty rate.